Short Communication: The most active fraction of red turi flowers (Sesbania grandiflora) on the cytotoxic activity of HepG2 cells - Sulasmi Sulasmi; OKID P. ASTIRIN; TETRI WIDIYANI (Nusantara Bioscience, 2020)
Abstract. Sulasmi, Astirin OP, Widiyanti T. 2020. Short Communication: The most active fraction of red turi flowers (Sesbania grandiflora) on the cytotoxic activity of HepG2 cells. Nusantara Bioscience 12: 68-72. Red turi flowers (Sesbania grandiflora L.Pers) contain many chemical compounds with high bioactivity. One of the chemical compounds is flavonoid compound. Quercetin is a class of flavonoid compound. This compound is obtained by extraction with methanol as a solvent then it is partitioned by water and ethyl acetate as a solvent. The fraction obtained is given phytochemical tests, which is further test using Thin Layer Chromatography (TLC) to detect the quercetin compounds. The level of flavonoid is determined using UV Vis spectrophotometer. Water and ethyl acetate fractions are tested cytotoxically using the MTT method (3-(4,5-dimethyltiazol-2-il)-2,5-diphenyltetrazolium bromide) with ELISA Microplate Reader. This study aims to determine the most active fraction of red turi flowers on the cytotoxic activity of HepG2 cells, which are model cells for liver cancer. The results of water fraction do not contain quercetin compounds, with IC50 value of 961.11µg/mL. The ethyl acetate fraction contains quercetin compounds with total flavonoid equivalent quercetin of 1.76% b/b and IC50 value of 149.15µg/mL. Ethyl acetate fraction is more active than the water fraction with moderate cytotoxicity.